Factors Influencing the Utilization Pattern of Kisan Mobile Advisory Service - K.V. Patil; V. T .Patel (Indian Journal of Extension Education, 2022)
The research was undertaken on 123 respondents of Banaskantha district of Gujarat state selected through multistage sampling method with the target to establish the relationship between farmer-subscribers’ profile characteristics and their Kisan Mobile Advisory Service (KMAS) utilization pattern. The data was collected using a structured schedule and the respondents were interviewed personally. The information was analysed with mean, standard deviation, frequency, percentage, multiple regression and stepwise regression for a meaningful interpretation. The multiple regression analysis indicated that the ‘Z’ values of age, education, scientific orientation, extension participation and attitude had essentially accorded in disclosing the variety to the utilization pattern of KMAS. The stepwise regression investigation showed that extension participation was the most (69.80%) impacting attribute for usage of KMAS. As such, these factors ought to be considered while determination of the farmers for execution of extension programmes